Long-term continuous treatment as a new strategy for relapsed or refractory multiple myeloma - S. V. Semochkin (Онкогематология, 2020)
The prognosis for patients with multiple myeloma has improved substantially over the past decade with the development of new, more effective chemotherapeutic agents and regimens, and improved management of toxicities. Treatment of relapsed or refractory multiple myeloma represents a vital aspect of the overall care for patients with multiple myeloma and a critical area of ongoing biologic and clinical research. The choice of regimen at relapse is usually based on the prior response, toxicities, assessment of prognostic factors, age and comorbidities of individual patients, their somatic condition and expected effectiveness and tolerability. The new drugs, such as ixazomib, carfilzomib, pomalidomide, daratumumab and elotuzumab in combinations in doublet or triplet regimens, have greatly increased the treatment armory against myeloma. Long-term continuous therapies as a new strategy for relapsed or refractory multiple myeloma have been shown to provide an eradicating of minimal residual disease and deep prolong responses, with the goal of improving progression-free survival and overall survival. The integration of novel agents into the treatment paradigm has shifted the perception of multiple myeloma from an incurable fatal disease to a manageable chronic one. This review discusses the most recent and effective regimens for the relapsed or refractory multiple myeloma treatment, based on the results of recently published phase II and III clinical trials. Analyses the current clinical trial data discussed with a focus on lenalidomide or bortezomib as a basis of new treatment regimens.